Cardiometabolic healthcare for men with prostate cancer: an MD Anderson Cancer Center experience - Andrew W. Hahn; Whittney Thoman; Efstratios Koutroumpakis; Amer Abdulla; Sumit K. Subudhi; Ana Aparicio; Karen Basen-Enngquist; Christopher J. Logothetis; Susan C. Gilchrist (Cardio-Oncology, 2023)
Abstract Background Men diagnosed with prostate cancer are at risk for competing morbidity and mortality due to cardiometabolic disease given their advanced age at diagnosis, high prevalence of pre-existing risk factors, and receipt of systemic therapy that targets the androgen receptor (AR). Expert panels have stressed the importance of cardiometabolic risk assessment in the clinic and proposed evaluating key risks using consensus paradigms. Yet, there is a gap in real-world evidence for implementation of comprehensive cardiometabolic care for men with prostate cancer. Methods This is a retrospective, descriptive study of patients with prostate cancer who were referred and evaluated in the Healthy Heart Program at MD Anderson Cancer Center, which was established to mitigate cardiometabolic risks in men with prostate cancer. Patients were seen by a cardiologist and exercise physiologist to evaluate and manage cardiometabolic risk factors, including blood pressure, cholesterol, blood glucose, tobacco use, and coronary artery disease, concurrent with management of their cancer by a medical oncologist. Results From December 2018 through October 2021, the Healthy Heart Program enrolled 55 men with prostate cancer, out of which 35 had biochemical, locoregional recurrence or distant metastases, while all received at least a single dose of a luteinizing hormone-releasing hormone (LHRH) analog. Ninety-three percent of men were overweight or obese, and 51% had an intermediate or high risk of atherosclerotic cardiovascular disease at 10 years based on the pooled cohort equation. Most men had an overlap of two or more cardiometabolic diseases (84%), and 25% had an overlap of at least 4 cardiometabolic diseases. Although uncontrolled hypertension and hyperlipidemia were common among the cohort (45% and 26%, respectively), only 29% of men followed up with the clinic. Conclusions Men with prostate cancer have a high burden of concurrent cardiometabolic risk factors. At a tertiary cancer center, the Healthy Heart Program was implemented to address this need, yet the utility of the program was limited by poor follow-up possibly due to outside cardiometabolic care and inconvenient appointment logistics, a lack of cardiometabolic labs at the time of visits, and telemedicine visits.